Black Ice and Yellow Snow: On Digging into Canuck Pulp Fiction. - Clarke, George Elliott (University of Toronto Quarterly, 2025)
One of the oddities of Canadian literary criticism – especially of the anglophone side – is its reluctance to canvass materials that revel in the shocking, the sensational, the scatological, the sordid, even if such revelling is conducted with consummate respect for highbrow, academic standards that must be met if the works in question are to be canonized upon university syllabi. This article maintains that Anglo Can-Lit critics look askance at Canadian "pulp fiction" genres (even Harlequin romances) because of the inherited, British, colonial-imperial predisposition to distrust materials "pandering" to popular taste as works that, pleasing the public, must be purple in prose, black in morals, yellow in paper quality, and pornographic blue in depicting sexuality. The point is proven in reference to case studies of the receptions of should-be (or could-be) canonical Can-Lit works: Marian Engel's novel Bear (1976), John Glassco's semi-fictionalized Memoirs of Montparnasse (1970), Dorothy Proctor (and Fred Rosen)'s "true crime" saga Chameleon (1994), Stephen Vizinczey's novel In Praise of Older Women (1965), and Stephen Williams's "true crime" work Invisible Darkness: The Strange Case of Paul Bernardo and Karla Homolka (1996). The long-term, Can-Lit, critical reaction to these texts foregrounding lust and bloodlust, crime and punishment, perversion and subversion seems to be a quiet dismissal following cordial accordance of due notoriety, despite the simultaneous acknowledgement of literary merit. Ultimately, the Anglo-Canuck penchant for disdaining "pulp" literature as outré (that is, "American") furthers the marginalization of already racially and/or sexually marginalized and/or (ex-)incarcerated and/or poverty-stigmatized Canadian writers.